UHF-generation in a coaxial slowing down structure filled with plasma - Markov, P.I.; Antipov, V.S.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2002)
Microwave generation by an electron beam in a coaxial transmission line in which the inner and outer conductors are both corrugated is studied theoretically. An annular electron beam propagates in a transport channel filled entirely with plasma. The results of nonlinear modeling of amplification of eigen waves in that structure are represented. The wave saturation amplitudes for various plasma densities are found. The influence of wave damping on the output power of this amplifier is studied. It is shown that the threshold current, at which one there is no amplification in whole wide passband.